Clostridium Difficile and COVID-19: Novel Risk Factors for Acute Portal Vein Thrombosis. (28th February 2021) - Rokkam, Venkata Ram Pradeep; Kutti Sridharan, Gurusaravanan; Vegunta, Rathnamitreyee; Vegunta, Radhakrishna; Boregowda, Umesha; Mohan, Babu P.
Abstract : The COVID-19 pandemic has created an unprecedented global health care crisis. COVID-19 patients are found to have increased thrombotic risk. Despite being on prophylactic anticoagulation, many develop serious arterial and venous thromboembolic events. Emerging reports indicate COVID-19 may be considered a novel risk factor for portal vein thrombosis. Although, intra-abdominal infections are identified as risk factors, clostridium difficile colitis has not been typically seen as a risk factor for PVT. We report a case of an elderly female with a recent diagnosis of COVID-19 and no prior history of cirrhosis or malignancy who presented with diarrhea due to clostridium difficile infection. She developed sudden onset severe abdominal pain during the course of hospitalization. Acute portal vein thrombosis was identified on CT imaging of the abdomen, and she improved well with therapeutic anticoagulation. Acute portal vein thrombosis usually results from a combination of local and systemic prothrombotic risk factors. The combination of local infection by clostridium difficile and COVID-19 coagulopathy led to development of portal vein thrombosis in our patient. To the best of our knowledge, this is the first case of portal vein thrombosis reported in a patient with clostridium difficile infection in the setting of COVID-19 coagulopathy. During the current pandemic, clinicians should strongly consider abdominal imaging in patients presenting with abdominal pain due to clostridium difficile infection in the setting of COVID-19 to rule out complications such as portal vein thrombosis. Early diagnosis and treatment of portal vein thrombosis prevent complications of portal hypertension and intestinal infarctions.